Handbook of manufacturing engineering and technology - Nee, A. Y. C. 1948- (Andrew Yeh Chris) (Springer London, 2015)
The Springer Reference Work Handbook of Manufacturing Engineering and Technology provides overviews and in-depth and authoritative analyses on the basic and cutting-edge manufacturing technologies and sciences across a broad spectrum of areas. These topics are commonly encountered in industries as well as in academia. Manufacturing engineering curricula across universities are now essential topics covered in major universities worldwide.